Management of Cystoid Macular Edema in Retinitis Pigmentosa. (2nd January 2017) - Huckfeldt, Rachel M.; Comander, Jason
ABSTRACT: Retinitis pigmentosa is a genetically heterogeneous disorder with an estimated prevalence of one in 4, 000 that is classically characterized by the progressive constriction of peripheral vision and a later deterioration of visual acuity. Central vision can be compromised earlier in disease, however, in the approximately 25% of patients that have cystoid macular edema. This poorly understood problem can thus significantly impair patient quality of life, particularly as available treatments have limited efficacy. We will review clinical features of retinitis pigmentosa-associated cystoid macular edema, potential causative mechanisms, and finally, evidence supporting currently employed therapies with emphasis upon which management strategies require further evidence-based evaluation.